The Meaning Of Malamang In Baralek In Nagari Alahan Mati Pasaman Regency - Atisa Aprilia; Suharti; Yurisman (Kirana Publisher (KNPub), 2024)
This study discusses the meaning of the malamang procession in the Nagari Alahan Mati community. The purpose of this study is to describe how the background of malamang at the baralek event in Nagari Alahan Mati and the meaning of the malamang procession at the baralek event in Nagari Alahan Mati. The theory used is symbolic interactionalist theory according to Blummer's understanding. The method used in this study is qualitative with an ethnographic approach. The data collection techniques are field observation, interviews, and documentation. The finding of this study is that the background of malamang at the baralek event came from Sheikh Burhanuddin's accident while conducting a banquet at a community home. The malamang tradition in the Nagari Alahan Mati community occurred in the 1950s. The malamang tradition is carried out by the Alahan Mati community the day before the baralek event, and a week before the host baralek event. Things that must be done, in terms of the division of labor in the malamang tradition is also distinguished by gender, men have the task of finding firewood and reeds for malamang, while women have the task of cooking lamang until cooking. The meanings in every malamang procession include mutual cooperation, silaturrahmi, and kinship.